PENGARUH KINERJA KEUANGAN DAN CORPORATE GOVERNANCE TERHADAP KEBIJAKAN DIVIDEN - Komaruddin (2022)
This study aims to examine and analyze the factors that influence LQ45 Indonesia Stock Exchange (IDX) companies in 2017-2020 in determining dividend policy in terms of financial performance and corporate governance. Financial performance is proxied by profitability and company growth, while corporate governance is proxied by independent commissioners and institutional ownership. Based on the purposive sampling method, 22 samples were studied in this study. Hypothesis testing using panel data regression with the help of the STATA application. From this study, it was found that (1) profitability has a significant effect on dividend policy, (2) company growth has no effect on dividend policy, (3) independent commissioners has no effect on dividend policy, and (4) institutional ownership has no effect on dividend policy.